THE EFFECT OF DEA COCAMIDE CONCENTRATION VARIATIONS ON PHYSICAL PROPERTIES OF PURPLE SWEET (Ipomea batatas L.) EXTRACT SOLID SOAP PREPARATIONS - Dewi - Rashati (JURNAL ILMIAH FARMASI AKADEMI FARMASI JEMBER, 2023)
Solid soaps are the most commonly used. The addition of various concentrations of Cocamide DEA is expected to fulfill the physical properties test of solid bath soap. The purpose of this study was to determine the effect of variations in the concentration of Cocamide DEA on the physical properties of solid soap. knowing how many concentrations of Cocamide Dea formulation that meet the physical properties test of solid soap. a pre-experimental (one group) post-test design was used for this research method. The ingredients used in this study were cocamide DEA, NaOH, purple sweet potato extract, 70% ethanol, olive oil, coconut oil, chewing gum fragrance, aquadest. The treatments in this study were various concentrations of Cocamide DEA F1 2%, F2 3%, F3 5%. Parameters observed were organoleptic test, pH test, water content test, foam height test. organoleptic results showed that F1, F2, F3 had a smooth texture, a strong bubble gum aroma, F1 was dark brown, F2 was brown, F3 was light brown. Results pH F1 9.4, F2 9.6 F3 9.8. The results of the water content of F1 0.02%, F2 0.03% F3 0.07%. High yield foam F1 7.0, F2 7.4, F3 7.8. Cocamide DEA with a concentration of 2% F1 which meets the physical properties test of solid soap.